Financial Distress Analysis to Predict Company Bankruptcy Using the Modified Altman Method - Ilyas, Muhammad; Sari, Ema; Umar, Fitriana (Almana : Jurnal Manajemen dan Bisnis, 2024)
Financial distress is a condition where the company experiences a decline in its financial condition before bankruptcy. To avoid this condition, the company must pay attention to its financial condition both in terms of its balance sheet and income statement using financial statement analysis techniques, such as the Altman model. The purpose of this study is to analyze the occurrence of Financial Distress to predict company bankruptcy using the Modified Altman method using 3 classification categories namely safe, gray, and distress. A quantitative approach was used in this study with a total population of all companies listed on the JII and the sample selection using a purposive sampling technique so that a sample of 13 companies was obtained. Based on the Altman Z-score analysis, the results show that: 8 companies are consistently in the Safe category for 5 years with a cut-off value> 2.9. Then, if analyzed as a whole, the mean value obtained from all companies is 5.7688> 2.9. This value illustrates that on average all companies listed on the Jakarta Islamic Index in 2018-2022 are in the safe category.